Supervisi Klinis untuk Meningkatkan Kemampuan Guru dalam Menyusun Naskah Soal Asesmen Madrasah - Saepuloh, Asep; Saepuloh (Jurnal Garasi Buku dan Obrolan Keilmuan, 2024)
This research aims to improve teachers' abilities in compiling good and correct madrasa assessment questions according to the rules. The specific objectives are to identify weaknesses in the three elements of question preparation (material, construction, and language), determine the elements that most need strengthening, and carry out evaluations for improvement. The research was conducted at MAS Integrated Ar Rahman Nasol Ciamis. Clinical supervision is carried out to assess the implementation of regulations in the field and find strengths and weaknesses. The research results show that there are still many errors in preparing the questions, so further guidance and training is needed.